The diagnostic of parenchimatous sialadenitis with the using of mrt - V S Bulgakov; A S Manvelyn; E S Beliseva; I W Gaiduk; S N Razumova; L G Worfolomeeva; L R Fahrislamova; L N Kolobkova (RUDN Journal of Medicine, 2008)
Diseases of salivary glands come to 3-24% of all dental pathology. In spite of considerable amount of observation methods of salivary glands, diagnostics of different forms of diseases stays difficult. We want to present you the capability of MRT for the diagnostics of parenchymatous sialadenitis.